Multi‐site N‐Glycan mapping study 2: UHPLC. Issue 7 (6th February 2018) - Szekrényes, Ákos; Park, SungAe Suhr; Cosgrave, Eoin; Jones, Aled; Haxo, Ted; Kimzey, Michael; Pourkaveh, Shiva; Szabó, Zoltán; Sosic, Zoran; Feng, Peng; Sejwal, Preeti; Dent, Kelsey; et al.
Abstract: In the first part of this publication, the results from an international study evaluating the precision (i.e., repeatability and reproducibility) of N‐glycosylation analysis using capillary electrophoresis of APTS‐labeled N‐glycans were presented. The corresponding results from ultra‐high performance liquid chromatography (UHPLC) with fluorescence detection are presented here from 12 participating sites. All participants used the same lot of samples, reagents, and columns to perform the assays. Elution time, peak area and peak area percent values were determined for all peaks ≥0.1% peak area, and statistical analysis was performed following ISO 5725‐2 guideline principles. The results demonstrated adequate reproducibility, within any given site as well across all sites, indicating that standard UHPLC‐based N‐glycan analysis platforms are appropriate for general use.